Spine Bracing: When to Utilize—A Narrative Review - John L. Cerillo; Alexander N. Becsey; Chai P. Sanghadia; Kevin T. Root; Brandon Lucke-Wold (Biomechanics, 2023)
Spinal bracing is a common non-surgical technique that allows clinicians to prevent and correct malformations or injuries of a patient’s spinal column. This review will explore the current standards of practice on spinal brace utilization. Specifically, it will highlight bracing usage in traumatic injuries, pregnancy, pediatrics, osteoporosis, and hyperkyphosis; address radiological findings concurrent with brace usage; and provide an overview of the braces currently available and advancements in the field. In doing so, we aim to improve clinicians’ understanding and knowledge of bracing in common spinal pathologies to promote their appropriate use and improve patient outcomes.